Analisis pengaruh arus pengerasan dan kecepatan pengelasan terhadap lebar manik las dan distorsi pada pengelasan gas metal arc welding (GMAW) dengan sambungan tumpul SS 304 - Ario Sunar Baskoro; Dhedhe Rodat Budi Prasetya; Agus Widyianto (Jurnal Teknik Mesin Indonesia, 2019)
In this study the influence of welding current and welding speed on weld bead width and distortion on blunt gas metal arc welding (GMAW) welding SS 304 has been carried out. The material used in this study was type 304 stainless steel (SS 304) with a butt joint configuration. The variation of GMAW welding parameters used are the welding current and the welding speed. The welding speed used are 115 A, 120 A and 125 A, while the welding speed used are 3.6 mm/s, 3.9 mm/s and 4.2 mm/s. The results of welding will be analyzed from the width of the weld bead and the distortion that occurs. Weld bead width and distortion are measured using Dino-Lite and Coordinate Machine Measure (CMM). The mean vertical displacement method is used to calculate longitudinal bending distortion and angular distortion. The results show that increasing the welding current will increase the width of the weld bead and distortion, but if increasing the welding speed will reduce the width of the weld bead and the distortion. The welding parameters of 125 A and 3.6 mm/s produced the largest upper and lower weld bead widths of 8.062 mm and 4.984 mm. The greatest longitudinal bending distortion and angular distortion are 1,748 mm and 4,076 degrees in the welding parameters of 125 A and 3.6 mm/s.